Sobor na Krovi - Sobor on the Blood - Ukrainian Institute of National Memory (2007)
The series "Sobor on the Blood" for the first time comprehensively and fairly will tell viewer about the struggle for unity and independence of our country for the period from 1919 to 1949. This struggle is considered in the series as a part of the all-European history.